Exploring the Impact of Home and School Environments on Students’ English Proficiency as Foreign Language - Adenin Nur Aliyah (Revorma: Jurnal Pendidikan dan Pemikiran, 2025)
This study aims to analyze the role of home and school environments in shaping English proficiency as a foreign language among eleventh-grade students at MAN 1 Kota Kediri. The main issue examined is how far the support and conditions from both home and school affect students’ English achievement. The research employed a descriptive survey method using a questionnaire focusing on two aspects: home environment support and school environment support. The respondents were 100 students selected through simple random sampling. The findings reveal that the home environment significantly contributes to students’ English learning through parental assistance, learning resources, and positive family attitudes toward English, even active parental encouragement remains limited. The school environment provides strong instructional and social support, especially through teacher feedback and extracurricular activities such as English clubs, yet lacks sufficient facilities and everyday English use within the school setting. Overall, the study concludes that synergy between home and school environments is essential to improve students’ English proficiency. It is recommended that parents become more actively involved in motivating their children, while schools enhance facilities and create a more immersive English atmosphere.